The Influence of Competency, Work Discipline and Work Environment on Employee Performance at The Special Guidance Institution for Class II Children in Bandung (LPKA Bandung) - Lusiana, Patarida Lonita; Rahmayanti, Rima (INOVASI, 2025)
This study aims to examine the influence of competence, work discipline, and work environment on employee performance at LPKA Class II Bandung. This study was motivated by the decline in LPKA employee performance as reflected in the results of the Main Performance Indicators (IKU) which showed a decline from 2021 to 2023. Problems found in interviews with employees related to performance include the lack of suitability of competence to tasks, work discipline problems, and a less supportive work environment. Based on the theory of Human Capital, work discipline, and work environment, this study uses a quantitative method with a descriptive approach to describe the variables studied. The results of the study show that competence, work discipline, and work environment have a significant positive influence on employee performance at LPKA Class II Bandung. Specifically, competence has a positive and significant effect on employee performance. Work discipline has also been shown to have a significant influence on improving performance, while a conducive work environment can increase employee efficiency and productivity. Simultaneously, these three variables have a significant effect on employee performance at LPKA Class II Bandung.